The importance of the enzyme Gamma-glutamyltransferase in the pathogenic cluster in type2 diabetic patient - Virgolici Bogdana; Dobre Maria Zinaida; Lixandru Daniela; Petcu Laura; Picu Ariana; Ionescu-Târgovişte Constantin; Greabu Maria; Bacanu Elena Violeta (Sciendo, 2024)
Introduction. Gamma-glutamyltransferase (GGT) is a liver enzyme involved in inflammation and oxidative stress. It is already known that MCP-1 (Monocyte Chemoattractant Protein-1) and TNF-α (tumour necrosis factor) as inflammatory markers, ICAM-1 (Intercellular Adhesion Molecule-1) as an endothelial dysfunctional marker, and glutathione, as an antioxidant, have abnormal levels in type 2 diabetic patients. The aim of this study was to evaluate the specific biological picture of type 2 diabetic patients that also associate higher GGT activity.